Detouring route of SMEs in post catching-up conditions: context and dilemmas behind the quest for science-based business model innovation. Issue 3 (2nd September 2022) - Wong, Chan-Yuan; Ni, Fu-Chuan; Sugano, Toshio
ABSTRACT: SMEs in post catching-up economies are assumed to possess high tech (science-based) business savvy with which to innovate new business models. Businesses operating without it are encouraged to commit and contribute to a coordinated R&D consortium – or risk missing the boat in the process of developing niches. In our view, it is fallacious to be preoccupied with coordinated joint R&D and patenting activities in construing the importance of science and leading SME growth agendas. This paper seeks to provide a rich and robust narrative, with the goal of bringing qualitative rigour to our typology and discovering contextual details that might be overlooked in proposing such development measures. We used two authoritative cases to uncover the dynamics and dilemmas of SMEs during times of change. This paper sheds light on why desirable results might not result from narrating the importance of science and intellectual capital for SMEs, or from seeding a routine for patenting and science-related business venturing. The inherent characteristics highlighted for traditional and IT-software based SMEs in Taiwan lead us to dwell deeper on what led to emergence of SMEs – and what could result from different industrial migration rates.